KONSEP ‘AQABAH DALAM TAŞAWWUF AL-GHAZĀLĪ: Tela’ah atas Kitab Minhāj al-‘Ābidīn - Yedi Purwanto (Jurnal Sosioteknologi, 2008)
Al-Ghazālī‟s complete name was Abū Hāmid Muhammad Ibn Muhammad Al-Ghazālī Al-Ţūsī (450-505H/1058-1111M). He contibuted greatly to the development of taşawwuf mastered the majority of Islamic traditional knowledge, such as Fiqh, Tafsir, Kalam and taşawwuf with his wide and deep knowledge at least in Muslim Sunni‟s perspective, he was considered, at least in Muslim Sunni prespective, as the most complete Muslim thinker who answered most at Islamic questions, especially in sufism. It is not surprising that his works, especially in sufism has exerted great the influences on Islamic world generally and Indonesia especially in interpreting sufi doctrines for long time. The influence of al-Ghazālī‟s thought can be seen from the great numbers of studies on sufism conducted by educated Muslim society from the Islamic boarding high school till university or college. With observing several works of al-Ghazālī thought in many boarding schools and the tendency for student college to study the thought of al-Ghazālī, the writer conclude that concerning religious matters Indonesian Muslim community have considered al-Ghazālī‟s works as reference more authoritative than the other thinkers in this field. Al-Ghazālī dominated the study of it in educated Indonesian Muslim are : Ihya‟ „Ulūm al-Dīn, Bidāyah al-Hidāyah and Minhāj al-„Ābidīn. These works had been translated into Indonesian language. Furthermore, the last two works have been explained with Arabic language, first the book „Bidāyah al-Hidāyah‟ by Nawawi Banten with title al-Marāqi al-„ubūdiyyah, secondly the book „Minhāj al-„Ābidīn‟ by Ihsān Ibn Muhammad Dahlān (d.1330H/1952M), a „alim from Jampes, Kediri with titled Sirāj al-Tālibīn. Al-Ghazālī‟s Minhāj al-„Ābidīn is interesting and very important to study. This book is a short composition but contains the esential doctrines (at sufism). It was the last work of al-Ghazālī before he passed away, just his extraordinary friends who listen directly from al-Ghazālī. This book summons its readers to reflect the essence of Ibādah (Worship) and its various steps to make it perfect. There are seven steps: 1) knowledge and gnosis (al-„ilm wa al-ma‟rifah), 2) repentance (al-tawbah), 3) permanent barriers (al-„awā‟iq), 4) temporary barriers (al-„awārid), 5) encouraging factors (al-khawf wa al-raja‟), 6) blaming spirit (al-qawādih) and 7) praising God (al-hamd wa al-shukr). The worship is the form of obedience and slavery at man to his Lord, so that worship would be most valuable thing which guides man to the heaven, but to reach a perfection in worship, a man must go through many blocks, and it needs sacrifice, al-Ghazālī called the stages and the barriers in worship with „Aqabah. The result of this research shown that in reality the whole difficulties which must be passed through by worshiper in his worship, the difficulties which must be faced is comparable with the path, full of barriers and temptations which can deviate the worshiper in his worship, „Aqabah in worship could only be through with a hard struggle of Mu‟min. With this theory al-Ghazālī wants to show us how to cope with all difficulties in worship. As far the method to pass through the „Aqabah are:] „Aqabah in knowledge and gnosis (al-„ilm wa al-ma‟rifah) can be throug by seeking for knowledge and education in theology, science of law, ethics, exact sciences, history, etc. „Aqabah in repentance (al-tawbah) is pass through by relizing bad effect of sins, the severe punishment of Allāh for sins doers and his weakness to defend from Allāh‟s punishment. „Aqabah in permanent barriers (al-„awā‟iq)is passed through by hard struggle to go through the many kind of barriers like the world, creation, men, devil, and desire which followed by praying for the help from Allāh. „Aqabah in temporary barriers (al-„awārid) is passed through by fearness and please to Allāh‟s windows. „Aqabah in encouraging factors (al-khawf wa al-raja‟) is passed through fearness and hope to Allāh SWT. „Aqabah in blaming spirit (al-qawādih), is passed through by sincerty of intention to Allāh SWT in worship. And „Aqabah in praising God (al-hamd wa al-shukr) is passed through by replacing our thank to Allāh SWT for his mercies and blessings He has given. Hopefilly this research will be useful as the sources information and the basic theory and practice in doing worship in accordance with Islamic shari‟ah. To apply or to implement this information in this research needs the practical measure to create a conducive environment for concentrating worship, in the form of institutions which can lead the education in good worship by applying „Aqabah Theory of al-Ghazālī.